English and Its Influence on Sundanese Communication among Generation Z in Bandung - Dasrun Hidayat; Nabila Damayani Marzaman; Rena Delianti; Sobia Shahzad (Komunikator, 2024)
The escalating use of English as a primary mode of communication in Bandung City is impacting the younger generation's interest in learning and using the Sundanese language. This quantitative study investigates the correlation between English and Sundanese language usage among 100 respondents aged 12-21, employing correlation and simple linear regression tests. Results indicate a negative influence of English on Sundanese usage, with higher English usage correlating with lower Sundanese use (correlation coefficient: -0.622, English's effect on Sundanese: 59.5%). The decline in Sundanese usage is attributed to environmental factors, education, and peer interactions. Recommendations include promoting Sundanese among Generation Z to preserve the language.